Akuntabilitas dan Amanah : Evaluasi Pengelolaan Dana Kurban Pada RT X di Kota Bekasi - Dewi Kurnia Indrastuti; Rinjani (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
Qurban funds are collected from individuals who want to perform qurban. The funds are managed by the organizing committee and used to purchase sacrificial animals to be distributed to eligible beneficiaries. This study evaluates the management of qurban funds by RT “X” in Bekasi City for the year 2026 to assess whether the process was carried out in an accountable manner. Data were collected through interviews and document reviews. These processes were conducted from early June to early July 2026. The findings indicate that all major stages of the process including fund collection, procurement of sacrificial animals, slaughtering, distribution of the meat, and the return of any remaining funds were implemented transparently and supported by adequate evidences, Drawing on Stewardship theory and The COSO Internal Contro Framework, this study recommends a clearer segregation of dusties among committee members, particularly in the area of fund management, procurement, and reporting. Strengthening the division of responsibility is expected to enhance the effectiveness of the committee’s operations while simultaneously promoting transparency, accountability, and good governance in the management of future qurban funds..